2012
DOI: 10.1016/j.expneurol.2012.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Improved rate of peripheral nerve regeneration induced by extracorporeal shock wave treatment in the rat

Abstract: De-focused low energy extracorporeal shock wave therapy (ESWT) has been widely used in various clinical and experimental models for the treatment of painful conditions such as epicondylitis and plantar fascitis and also bone and wound healing. There is evidence that ESWT improves the metabolic activity of various cell types, e.g. chondrocytes and endothelial cells but little is known about its effects on nervous tissue. The aim of this study was to investigate whether ESWT improves the regeneration of injured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
79
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(81 citation statements)
references
References 31 publications
0
79
1
1
Order By: Relevance
“…In a study that investigated the effect of the early application of ESWT on nerve regeneration, nerve conduction velocity and amplitude increased more in the group that received ESWT immediately after sciatic nerve impairment than in the control group (Hausner et al 2012). In another study of the effect of ATF3 and GAP-43 on the regeneration of neurons, their expression was significantly increased in the ESWT group compared with a control group (Murata et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In a study that investigated the effect of the early application of ESWT on nerve regeneration, nerve conduction velocity and amplitude increased more in the group that received ESWT immediately after sciatic nerve impairment than in the control group (Hausner et al 2012). In another study of the effect of ATF3 and GAP-43 on the regeneration of neurons, their expression was significantly increased in the ESWT group compared with a control group (Murata et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…confirmed similar findings and revealed that multiple sessions of low-energy ESWT would provide a longer-lasting effect. Hausner et al 35. reported that low-energy ESWT could induce a significant recovery of nerve regeneration and amplitude in rats treated with nerve autograft of the sciatic nerve, and that the effect is most remarkable at 8 weeks after the nerve injury.…”
Section: Discussionmentioning
confidence: 99%
“…In clinics, beneficial effects of ESWT in vivo have been observed in treatment of non-union fractures [24e26], ischemia-induced tissue necrosis [27], peripheral nerve lesions [28], chronic wounds [29,30] and several other fields [31e33].…”
Section: Introductionmentioning
confidence: 99%